Early diagenetic constraints on Permian seawater chemistry from the Capitan Reef. (1st July 2022) - Bryant, Roger N.; Present, Theodore M.; Ahm, Anne-Sofie C.; McClelland, Harry-Luke O.; Razionale, Dan; Blättler, Clara L.
Abstract: The Capitan Reef Complex in West Texas is famous for its high prevalence of early marine cements, unusual for a Phanerozoic platform, leading some to suggest that Precambrian styles of carbonate sedimentation enjoyed a Permian encore. Here, we use patterns of stable Ca, Mg, C and S isotopes to better understand the environmental driver(s) of the enigmatic cementation. We find that calcite that is the most enriched in 44 Ca has δ 34 S values that approach the inferred composition of Permian seawater sulfate. Microbial sulfate reduction in pore fluids must have been spatially and temporally coincident with recrystallization of primary carbonate phases, such that substantial 34 S-enriched sulfate was incorporated into diagenetic calcite under relatively closed-system conditions. Moreover, the magnitude of 34 S-enrichment of carbonates relative to seawater was strongly influenced by local diagenetic conditions, with fluid-buffered early marine cements, shelf, reef, and upper slope preserving more seawater-like S isotope ratios than the more sediment-buffered lower slope. Some samples are far more 34 S-enriched relative to seawater than those from modern sites in similar depositional environments, possibly responding to specific combinations of sedimentary parameters (e.g., grain size, porosity, organic matter rain rate). Additionally, the sulfate concentration in the Delaware Basin might have been slightly lower than modern levels, leading to more extensive isotopic evolution of sulfate in pore waters during carbonate recrystallization. Based on the data and a numerical model of carbonate recrystallization, we suggest that one driver of the extensive seafloor cement precipitation in the Capitan Reef Complex was a Permian water column [Ca 2+ ]:[SO4 2− ] ratio somewhere between 1 and modern seawater.